Accuracy of loop-mediated isothermal amplification for diagnosis of human leptospirosis in Thailand. - Sonthayanon, P; Chierakul, W; Wuthiekanun, V; Thaipadungpanit, J; Kalambaheti, T; Boonsilp, S; Amornchai, P; Smythe, L; Limmathurotsakul, D; Day, N; Peacock, S (2011)
There is a lack of diagnostic tests for leptospirosis in technology-restricted settings. We developed loop-mediated isothermal amplification (LAMP) specific for the 16S ribosomal RNA gene (rrs) of pathogenic and intermediate group Leptospira species. The lower limit of detection was 10 genomic equivalents/reaction, and analytical specificity was high; we observed positive reactions for pathogenic/intermediate groups and negative reactions for non-pathogenic Leptospira species and other bacterial species. We evaluated this assay in Thailand by using a case-control study of 133 patients with laboratory-proven leptospirosis and 133 patients with other febrile illnesses. Using admission blood, we found that the rrs LAMP showed positive results in 58 of 133 cases (diagnostic sensitivity = 43.6, 95% confidence interval [CI] = 35.0-52.5) and in 22 of 133 controls (diagnostic specificity = 83.5, 95% CI = 76.0-89.3). Sensitivity was high for 39 patients who were culture positive for Leptospira spp. (84.6, 95% CI = 69.5-94.1). The rrs LAMP can provide an admission diagnosis in approximately half of patients with leptospirosis, but its clinical utility is reduced by a lower specificity.